Integrated logistics for colombian development way for competitiveness: the double railway roads - García-Sierra, Jaime Alberto; García-Cabana, Andrea Carolina (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2010)
This article emphasizes on the importance of rail transportation as a connecting and integratingelement of the national production coming from different sectors of the conomy.Apart from maritime transportation, railroad transportation is the kind of transportation that guarantees long-term sustainability at relatively low rates if compared to land and fluvial transportation. These reasons are thought to be enough to contribute to the market efficiency and international competitiveness. More than 70% of the national production would move through this means clearing the roads, improving its utilization and optimizing its use. This paper highlights the need of generating a more balanced development between the rural and urban sectors of society, without making detailed and critical analysis of the scientific economy. Thus, it is necessary to design again the demographic and territorial planning of Colombia by redistributing the population that belongs to the misery belts found in the main Colombian cities. This may be achieved by applying a policy contrary to the one suggested by Currie Lauchlin in his Accelerated Economic Development in 1968 which stimulated the exodus of peasants towards the urban centers and discouraged politics against rural development that leaves the community homeless and easy prey for violent organizations as guerrillas, paramilitary or drug-dealers forcesNow that the end of the armed conflict seems to be close, we have to be prepared for the post conflict new relations and one of the strategies is to come back to the countryside with a real and effective institutional presence. To do so, we should begin with an effective security that guarantees a lasting peace. This new redistribution of the population requires an efficient integrative infrastructure that assures competitiveness of national production. Thanks to a modern railroad transportation system, we could attain this goal. This  ̈new ̈ proposed railroad designs of double lanes integrates the whole country from south to north and from east to west with different connections of international type. They would include two connections by the south with Ecuador, a connection by the northwest with Panama, by the northeast with Venezuela and by the east with Venezuela and possibly with Brazil. It is of great importance the connection between Medellin and Turbo, and Turbo-Bahia Cupica, on the condition that the territories nearby must be completely protected and preserved as a natural reserve or national parks, as it was recommended by socio-environmental studiesThe construction of Metro systems of transport in the main Colombian cities implies a high debt that involves the entire nation budget; while the investment in the double lane rail road’s is really reliable, since the nation gets a good profit from it and it benefits the total dimension toward the country ́s integral development.